2001
DOI: 10.4049/jimmunol.166.11.6633
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathway Regulating Lipopolysaccharide-Induced Shock by ST2/T1 Via Inhibition of Toll-Like Receptor 4 Expression

Abstract: ST2/ST2L, a member of the IL-1R gene family, is expressed by fibroblasts, mast cells, and Th2, but not Th1, cells. It exists in both membrane-bound (ST2L) and soluble forms (ST2). Although ST2L has immunoregulatory properties, its ligand, cellular targets, and mode of action remain unclear. Using a soluble ST2-human IgG fusion protein, we demonstrated that ST2 bound to primary bone marrow-derived macrophages (BMM) and that this binding was enhanced by treatment with LPS. The sST2 treatment of BMMs inhibited pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
205
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(220 citation statements)
references
References 33 publications
8
205
1
5
Order By: Relevance
“…33 Aside from its role in directing Th2-type responses, ST2L also has a well-characterized inhibitory effect on MyD88-dependent TLR activation. 17,49,50 Although TLR activation can promote Th2-type allergic inflammation, 51 targeting TLR9 with CpG has proved to be a highly effective therapeutic approach in experimental asthma. 52 The containment of Aspergillus in the allergic host requires TLR9 expression, 30 and exogenous CpG reverses fungal asthma when administered at a dose of 50 g for 2 weeks by intranasal, but not i.p., injection.…”
Section: Discussionmentioning
confidence: 99%
“…33 Aside from its role in directing Th2-type responses, ST2L also has a well-characterized inhibitory effect on MyD88-dependent TLR activation. 17,49,50 Although TLR activation can promote Th2-type allergic inflammation, 51 targeting TLR9 with CpG has proved to be a highly effective therapeutic approach in experimental asthma. 52 The containment of Aspergillus in the allergic host requires TLR9 expression, 30 and exogenous CpG reverses fungal asthma when administered at a dose of 50 g for 2 weeks by intranasal, but not i.p., injection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that sST2 protein could be involved in the inflammatory response as well as in Th2 immune responses [43,44]. Some evidence suggests that sST2 could act as an anti-inflammatory mediator, through a mechanism that involves the inhibition of Toll-like receptor signaling by sequestration of MyD88 and Mal adapter proteins [45,46] or inhibition of I-κB degradation [47] resulting in down-regulation of NF-κB. In vitro and in vivo experiments have shown that sST2 protein or an ST2-fusion protein is able to attenuate the production of pro-inflammatory cytokines IL-1β, TNF-α, IL-6, and IL-12 [30,45,48].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that sST2 could act as an anti-inflammatory mediator, through a mechanism that involves the inhibition of Toll-like receptor signaling by sequestration of MyD88 and Mal adapter proteins [45,46] or inhibition of I-κB degradation [47] resulting in down-regulation of NF-κB. In vitro and in vivo experiments have shown that sST2 protein or an ST2-fusion protein is able to attenuate the production of pro-inflammatory cytokines IL-1β, TNF-α, IL-6, and IL-12 [30,45,48]. In two mouse models of ischemia/reperfusion, pretreatment with an sST2-Fc fusion protein decreased the inflammatory response [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NCX by Na 1 -free medium induced the release of TNF-a from macrophages comparable to that caused by LPS (1 mg/mL) used as a positive control (Fig. 8A) [47]. This occurred equally in cells maintained in Na 1 -free medium for the entire time-period (4 h) and in cells exposed to Na 1 -free medium Figure 7.…”
Section: Effect Of Cb-dmb On the [Ca 21 ] I Increase Induced By Histamentioning
confidence: 68%